MONAS SEBAGAI SIMBOL PERJUANGAN BANGSA INDONESIA - Susilo, Susilo; Suryaningsih, Angelia Rantya Apriliawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2015)
The National Monument is a national symbol to symbol of Jakarta Year 1953-1975. The issues presented in this report is how the historical background of the emergence of the idea or the idea of building the National Monument in Jakarta, and the realization of the construction of the National Monument as a national symbol of Indonesia in transit, and Soekarno role in the development of the National Monument. Also discussed is the view of society in defining post-construction National Monument National Monument. Using the method of writing a critical history that includes four steps namely the collection of primary and secondary sources, which consists of source criticism eksteren criticism and internal criticism that has authenticity and credible source. Interpretation of facts and events of the last re-writing of history by descriptive analysis. After National Monument formed physically, then in 1964 the Government of Andhra Pradesh to use National Monument as part of a symbol of the city. This turned out to cause a shift in the meaning of the National Monument. Society no longer interpret the National Monument as a national symbol but as a symbol of the city. The shift is happening is the meaning of the National Monument became a symbol of the national symbol of the city. Keywords: National Monument,Tourism Spot, Jakarta City